Breathing Sound Detection from The External Auditory Canal with Condenser Microphones - Puripak Chunhakam; Panwit Tuwanuti; W. Sangpisit; Paramote Wardkien (My University, 2021)
Breathing disorders or sleep apnea is one of the major causes of death that can be diagnosed through breathing while the patient is asleep. At present, breathing detectors are inconvenient for wearing and annoying in the activity of daily life. Therefore, in this research, we present a method for detecting the respiratory sound of breathing from the external auditory canal. This sound is produced by the flowing of air through the respiratory tract and the sound travel through the eardrum to the organs to the external auditory canal by using a condenser microphone to detect the sound of inhalation and exhalation, the detector is shaped like an earphone which does not disturb sleep and does not cause a nuisance to the wearer. Because we are already used to wearing headphones for listening to music while sleeping. This proposed breathing detection system prototype consists of a condenser microphone, amplifier, and signal processing was performed by using the MATLAB program to detect the peak of the breath signal and interpret the peak of the signal as breathing. The results showed that the system can accurately monitor the breathing with an error of about 9.81%.
Keywords: Non-Invasive Vital Sign Monitoring; Obstructive Sleep Apnea Research; Phonocardiography and Auscultation Techniques